Enhancing biolistic plant transformation and genome editing with a flow guiding barrel - Connor Thorpe; Weifeng Luo; Qing Ji; Alan L. Eggenberger; Aline S. Chicowski; Weihui Xu; Ritinder Sandhu; Keunsub Lee; Steven A. Whitham; Yiping Qi; Kan Wang; Shan Jiang (Nature Communications)
Abstract The biolistic delivery system is an essential tool in plant genetic engineering, capable of delivering DNAs, RNAs, and proteins independent of tissue type, genotype, or species. However, its efficiency and consistency remain longstanding challenges despite decades of widespread use. Here, through advanced simulations, we identify gas and particle flow barriers as the root cause of these limitations. We show that a flow guiding barrel (FGB) achieves a 22-fold enhancement in transient transfection efficiency, a 4.5-fold increase in CRISPR-Cas9 ribonucleoprotein editing efficiency in onion epidermis, and a 17-fold improvement in viral infection efficiency in maize seedlings. Furthermore, stable transformation frequency in maize using B104 immature embryos increases over 10-fold, while in planta CRISPR-Cas12a-mediated genome editing efficiency in wheat meristems doubles in both T0 and T1 generations. This study provides insights into the fundamental mechanisms underlying biolistic inefficiency and demonstrates a practical solution that enables broader and more reliable applications in plant genetic engineering.